PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, UMUR OBLIGASI DAN UKURAN PERUSAHAAN TERHADAP PERINGKAT OBLIGASI PADA SEKTOR KEUANGAN YANG TERDAPAT DI BEI TAHUN 2015-2018 - Akhmad Darmawan; Yudith Foran Al Fayed; Fatmah Bagis; Bima Cininttya Pratama (Derivatif : Jurnal Manajemen, 2020)
This study aims to examine the effects of profitability, liquidity, leverage, age of bondsand firmsize toward bond ratingin the financial sectors listed inIndonesia Stock Exchangeduring2015-2018using 86 samples chosen bypurposive sampling. Meanwhile, data analysis techniques used in this study were descriptive statistics,classic assumption tests, multiple linear regression analysisand hypothesis testing. The results of data analysis using regression analysis showed that profitability had not a significant negative effect on bond ratingin financial sectors, liquidity had a significant positive effect on bond ratings in financial sectors, leverage had a significant positive effect on bond rating in financial sectorand ageof bondhad a significant negative effect on bond ratingin financial sectors. While, firmsize had a significant negative effect on bond ratingin financial sectors.Keywords:Profitability, Liquidity, Leverage, Age of Bonds, FirmSize, Bond Rating